CHARACTERISTICS OF LEARNING THEORIES IN EDUCATION ACCORDING TO PSYCHOLOGICAL DEVELOPMENT - Alfiyanto, Afif; Walidin, Warul; Mahmud, Salami (Jurnal Konseling Pendidikan Islam, 2024)
This study aims to determine the characteristics of learning theories in education according to psychological development. The method used is a literature review. Based on the researcher's analysis results, it is known that the flow of learning theories has different characteristics, even if the results are emphasized more than the learning process. Examples are 1) the cognitive flow, which emphasizes the learning process; 2) the humanistic school, which emphasizes the content of the lesson; 3) The flow of cybernetics which emphasizes the information system of the material being studied, and many other theories with unique characteristics. The different characteristics of various learning theories are due to 1) different types of learning, 2) learning motivation is low and has many stages, and 3) learning has the nature of skills and abilities and is rational. So to assess whether the opinions conveyed by various experts are accurate based on the flow of learning theory, it can be seen from the unique characteristics appropriate to the learning types.